Odorous Sulfur Compounds Emitted during Production of Compost Used as a Substrate in Mushroom Cultivation - Derikx, P. J. L. (1990)
Large-scale composting facilities are known to cause environmental problems, mainly through pungent air emitted by composting material. In air samples taken above stacks set up to prepare compost used as a substrate in mushroom cultivation, several volatile compounds were identified by means of the coupled techniques of gas chromatography and mass spectrography. Among the compounds identified, sulfur-containing compounds [H(2)S, COS, CH(3)SH, CS(2), (CH(3))(2)S, (CH(3))(2)S(2), and (CH(3))(2)S(3)] are the most conspicuous in causing a nuisance. Quantification of these compounds was performed by concentrating a relatively small air sample on Tenax GC. The sampling method appeared to be very useful under field conditions. During the composting process, the concentration of the volatile sulfur compounds in emitted air ranged from 1 to 35 μmol/m(3). The highest concentrations were obtained at the end of the outdoor process. Total sulfur emission amounted to 8.3 mg of sulfur per kg (fresh weight) of compost. The end product still contained 2.58 g of sulfur per kg (fresh weight) of compost. Suggestions about the origin of the volatile sulfur compounds are made.